Gambaran Tingkat Isolasi Sosial Siswa SMA Negeri di Makassar - Yuyun Nurmaliyah; Sahril Buchori; Zulfikri Zulfikri; Syahril Syahril (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the level of social isolation among students at a public high school in Makassar. This study employs a quantitative, descriptive approach. The study population consisted of 82 students in grades 10 and 11 at a public high school in Makassar, with a sample of 20 students selected through purposive sampling. Data collection was conducted using an adapted social isolation questionnaire consisting of 31 items on a Likert scale. Data analysis was performed using descriptive statistics in the form of percentages and categorical distributions. The results indicate that the majority of students fall into the moderate social isolation category (76%) and the high category (24%), with no students in the very high or low categories. These findings indicate that students’ social interactions in the context of this study have not developed optimally, as evidenced by a tendency to withdraw and a lack of participation in group activities. The implications of this study highlight the importance of the role of guidance and counseling services in developing intervention programs focused on improving students’ social skills, self-confidence, and the quality of their interpersonal relationships.